(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

f(x)=x(x^{2}-4)^{1/2}

2. Relevant equations

3. The attempt at a solution

so I started by, let,

u=x

u'=1

v=(x^{2}-4)^{1/2}

v'=1/2(x^{2}-4)^{-1/2}(2x)

so using the product rule

f'(x)= (x^{2}-4)^{1/2}+x(1/2(x^{2}-4)^{-1/2}(2x))

=(x^{2}-4)^{1/2}+x^{2}(x^{2}-4)^{-1/2}

Now do I just differentiate the second term again Im not quiete understanding what needs to be done here??

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Need help finding the derivative of this function!

**Physics Forums | Science Articles, Homework Help, Discussion**